Lightweight design of multi-stitched composite crash absorbers to improve specific energy absorption capability under quasi-static and impact loading - Rabiee, Ali (Cranfield University, 2018)
A comprehensive numerical and experimental study was performed to investigate the energy absorbing capabilities of glass/epoxy and carbon/epoxy members that could serve as stanchions in the subfloor structure of aircraft or rotorcraft. Circular cross sections with chamfered-ends failure trigger mechanism were investigated under axial and off-axis loading conditions. The optimal configuration that resulted in the highest possible specific energy absorption (SEA) was identified, which was at axial loading. The parameters in off-axis loading conditions that affected energy absorption capability were identified. Several cases were experimentally studied to cancel off-axis (oblique) loading effect. To increase interlaminar fracture toughness, stitching through the thickness was considered. Single, multi and pattern-stitching were studied to increase energy absorption capability of GFRP composite sections. The failure mechanisms, crushing process and force-displacement curve diagram of each case was studied to establish the effect of stitching on energy absorption capability. A correlation between stitching location and localised and global increase of energy absorption was established. It was identified, that the closer the stitching locations are, the higher the localised peak load becomes, and it influences the Mode-I crack propagation (main central crack) resistance, bending of fronds and friction, consequently, pattern-stitching resulted in a 15% increase in specific energy absorption capability (SEA) under quasi-static loading. Similarly, this stitching pattern resulted in a 14% increase in SEA using CFRP sections. Under impact loading, it was identified that pattern-stitching through the thickness resulted into 17% and 18% increase in SEA using GFRP and CFRP sections, respectively. Finite element models were also developed to simulate the crushing behaviour of the CFRP and GFRP sections observed experimentally under axial, off-axis, quasi-static and impact loading conditions. A multi-layer modelling methodology was developed by determining the most effective element size, number of shells, formulation, contact definitions, delamination interface, material model, friction and trigger mechanism. This approach captured the failure process, predicted the SEA and sustained crush load quite accurately within 5% error. Stitching through the thickness was modelled using an energy-based contact card to implement stitched and non-stitched Mode-I and Mode-II energy release rate parameters. This method accurately predicted stitched composite sections with 3% error compared with experimental data. Such modelling could thus support the future design of aircraft stitched and non-stitched stanchions within reasonable computer efficiency and accuracy.
Keywords: LS-DYNA; multi-stitches; crack resistance; oblique; off-axis loading; crashworthiness; through-thickness stitching